1985
DOI: 10.1159/000128458
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Ischaemia and Anastomotic Healing

Abstract: The leakage rate of colonic anastomoses may be as high as 13%. A good blood supply is of paramount importance. However tissue perfusion may be at risk in the elderly and in low colorectal anastomoses. We have tested the effect of isoxsuprine, an agent which reduces blood viscosity, and is an α-adrenergic antagonist and β-adrenergic agonist, on the healing process in normal and ischaemic rat colon. Both bursting pressure and hydroxyproline concentration were significantly improved in compromised ischaemic colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Blood flow is required for normal oxidative function of neutrophils, leukocyte activation, fibroblast production, angiogenesis and re-epithelization, which are essential for wound healing [4]. Our results correlate with many experimental studies which showed that ischemia impairs anastomotic wound healing [2,[4][5][6][7]. Bursting of all anastomoses in group 3 from the anastomotic line on the 7th day showed that anastomotic wound healing had not yet been completed.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Blood flow is required for normal oxidative function of neutrophils, leukocyte activation, fibroblast production, angiogenesis and re-epithelization, which are essential for wound healing [4]. Our results correlate with many experimental studies which showed that ischemia impairs anastomotic wound healing [2,[4][5][6][7]. Bursting of all anastomoses in group 3 from the anastomotic line on the 7th day showed that anastomotic wound healing had not yet been completed.…”
Section: Resultssupporting
confidence: 74%
“…The risk of anastomotic dehiscence of colonic anastomosis has been reported to be 13% [2]. Ischemia is the major cause of colonic anastomosis impairment [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important prerequisite, however, for the healing of the bowel wound is an adequate blood supply. Foster et al [15] compared anastomoses in the normal and in the devascularized colon of the rat after 5 days by bursting pressure examination. He measured 290 and 180 mm Hg, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…5] or by induction of a traumatic hypovolemic shock [5][6][7], In both models the degree of localized bowel ischemia is dif ficult to standardize due to systemic effects of these proce dures.…”
Section: Discussionmentioning
confidence: 99%